EVALUATION OF FUNGICIDES AGAINST FUSARIUM FRUIT ROT OF CITRUS - T. T. BARIA; R. K. PATIL (The Bioscan, 2018)
various fungicides screened were found superior in inhibiting the mycelial growth of F. pallidoroseum over control in vitro. Carbendazim, carbendazim (12 %) + mancozeb (63 %), thiophanate methyl and propiconazole at both the concentrations completely inhibited the mycelium growth (100 %) over control. The next best treatment in order of merit was Azoxystrobin (18.2 %) + difenoconazole (11.4 %) at 500 (78.80 %) and copper oxychloride at 1000ppm (85.48 %) concentrations, respectively over control.The Fusarium rot severity was significantly lowest in fruits treated with carbendazim at 500 and 1000 ppm concentrations in pre- (9.56 & 4.63 %) and post-inoculations (11.23 & 6.76%) followed by carbendazim (12 %) + mancozeb (63 %)(10.26 & 4.96) and (12.80 & 7.86 %) in pre-and post-inoculation treatments, respectively after 8 days of inoculation. The higher concentration (1000 ppm)of carbendazim found best for reducing the Fusarium rot severity (4.63 %) as compared to lower concentration (500 ppm) (9.56 %) in pre- and post-inoculation (11.23 %) treatments after 8th day of inoculation. Cymoxanil (8 %) + mancozeb (64 %) found least effective in controlling the rot at both the concentrations in pre- (23.73 & 18.76%) and post-inoculation (24.26 & 22.43%) treatments.